Time to Wake-Up: Extending the Window for Management of Unknown-Onset Strokes. Issue 1 (January 2021) - Fawaz, Al-Mufti; Wu, Sarah; Viswanathan, Divya; Kaur, Kavneet; Nuoman, Rolla; Nuoaman, Halla; Adnan, Yasir Ammar; Gandhi, Chirag D.; Kurian, Christeena; Sahni, Ramandeep
Abstract : The term "Wake-Up Stroke" is applied to a patient who displays no symptoms before sleep, but wakes with neurologic deficits suggestive of stroke. The current guidelines for acute ischemic stroke limit intravenous tissue plasminogen activator use to stroke patients in whom symptom onset or last known well is less than 4.5 hours. Approximately one-third of acute ischemic stroke patients present with unknown time of symptom onset and are often not eligible for intravenous reperfusion therapy in clinical practice. This review provides an overview of several earlier trials that used advanced neuroimaging to determine eligibility for reperfusion therapy in patients with unknown stroke onset. The reassuring results of these earlier trials that led to recent thrombolysis trials specifically targeted at "wake-up stroke" patients are discussed in this review. Ongoing studies aim to expand our knowledge regarding the safety and efficacy of thrombolysis in these patients.